Utilization of Social Media Platform Instagram as Participatory Design Tools in Indonesia - Leksono, Fitorio Bowo; Wisesa, Toufiq Panji (Idealogy Journal; Vol 5 No 2 (2020): Idealogy Journal (September 2020), 2020)
Indonesia as the biggest archipelago country in the world has problem for the implementation of participatory design, especially due to the poor communication infrastructure and the distance between host and users. On the other hand, Indonesia has more than 100 million of internet users. In addition, Indonesian also social media savvy with Facebook, Instagram and Twitter serve as the top 3 social media platform in Indonesia. This study explores the potential of Instagram to serve as Participatory Design tools through experimentation method. The outcome of this study is conclusion that will serve as guideline for any Participatory Design initiative in the future. Keywords: Instagram, Participatory Design, Indonesia